2021
DOI: 10.1002/anie.202109744
|View full text |Cite
|
Sign up to set email alerts
|

Tris(pentafluorophenyl)borane‐Catalyzed Carbenium Ion Generation and Autocatalytic Pyrazole Synthesis—A Computational and Experimental Study

Abstract: In recent years, metal-free organic synthesis using triarylboranes as catalysts has become a prevalent research area. Herein we report a comprehensive computational and experimental study for the highly selective synthesis of Nsubstituted pyrazoles through the generation of carbenium species from the reaction between aryl esters and vinyl diazoacetates in the presence of catalytic tris(pentafluorophenyl)borane [B(C 6 F 5 ) 3 ]. DFT studies were undertaken to illuminate the reaction mechanism revealing that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…3 In 2017, we reported the highly sensitive adduct Ph 2 C(N 2 )B(C 6 F 5 ) 3 4 suggesting that frustrated Lewis pairs (FLPs) might provide an avenue for main group capture of N 2 . While subsequent work by Melen applied borane activation of diazomethanes to organic synthesis, 5,6 we showed that reduction of such adducts generated radicals that effected C–H bond activations 7 and demonstrated that the FLP (C 6 F 5 ) 2 BOP t Bu 2 captured diazomethane to give robust adducts. 8 In addition, we have shown that the corresponding reactions of chloro-diazirene with FLPs effect NN cleavage.…”
mentioning
confidence: 84%
“…3 In 2017, we reported the highly sensitive adduct Ph 2 C(N 2 )B(C 6 F 5 ) 3 4 suggesting that frustrated Lewis pairs (FLPs) might provide an avenue for main group capture of N 2 . While subsequent work by Melen applied borane activation of diazomethanes to organic synthesis, 5,6 we showed that reduction of such adducts generated radicals that effected C–H bond activations 7 and demonstrated that the FLP (C 6 F 5 ) 2 BOP t Bu 2 captured diazomethane to give robust adducts. 8 In addition, we have shown that the corresponding reactions of chloro-diazirene with FLPs effect NN cleavage.…”
mentioning
confidence: 84%
“…This was found both experimentally and computationally (Figure 1). 31,34,35 By DFT studies the C-N bond in the boroncoordinated diazo-ester is longer and weaker (1.334 Å) than in the free uncoordinated diazo-ester (1.318 Å). 14 In addition, a shortening of the C−C bond length from 1.470 Å to 1.436 Å was also observed for the O→B adduct.…”
Section: Diazo Activation Using Catalytic B(c6f5)3mentioning
confidence: 99%
“…In 2021, Melen and co‐workers [61] provided the results of a thorough theoretical and experimental investigation into the highly selective synthesis of N ‐substituted pyrazoles 120 . The reaction of aryl esters 119 and vinyl diazoacetates 114 in the presence of tris(pentafluorophenyl)borane delivered the targeted products 120 in 70%–81% yields.…”
Section: Synthesis Of Pyrazole Derivatives From αβ‐Unsaturated Carbon...mentioning
confidence: 99%